2022
DOI: 10.1021/acs.cgd.2c00970
|View full text |Cite
|
Sign up to set email alerts
|

Toward White Light Random Lasing Emission Based on Strained Nano Polygermanium Doped with Tin via Metal-Induced Crystallization (MIC)

Abstract: Solubility of Sn in Ge network gives it a preference for photonic applications, because of the direct transition in GeSn alloy. Here, we employed the metal-induced crystallization (MIC) process of amorphous Ge and Si via Sn as a novel mechanism to incorporate Sn inside Ge and Si networks. (Al/Si/Sn/Ge/Sn) and (Al/Ge/Sn/Ge/Sn) multilayers are deposited by thermal vacuum evaporation on different substrates. The devices are annealed under low vacuum at 500 °C to incorporate the oxygen for band-gap tuning. The str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 98 publications
(185 reference statements)
0
4
0
Order By: Relevance
“…Characterizing the semiconducting crystals for inelastic scattering phenomena using Raman spectroscopy has gained attention over decades to analyze the structural and the vibrational properties. 54,55 Strain state in a crystal lattice is determined using non-destructive Raman measurements as an immediate application in electronic and photonics. 55 The frequency of quanta of vibrations, i.e., phononic frequencies, are observable only for the long wavelength (k = 0) Ge-Ge LO phonon modes in (100) oriented cubic semiconductor crystals.…”
Section: Resultsmentioning
confidence: 99%
“…Characterizing the semiconducting crystals for inelastic scattering phenomena using Raman spectroscopy has gained attention over decades to analyze the structural and the vibrational properties. 54,55 Strain state in a crystal lattice is determined using non-destructive Raman measurements as an immediate application in electronic and photonics. 55 The frequency of quanta of vibrations, i.e., phononic frequencies, are observable only for the long wavelength (k = 0) Ge-Ge LO phonon modes in (100) oriented cubic semiconductor crystals.…”
Section: Resultsmentioning
confidence: 99%
“…36,43 This gives these p–i–n structures the chance to serve as optically pumped white light and NIR source. 15 It is observed that the heterostructures containing Si layer have higher intensity of PL peak due the enhancing of Si in MIC process of Ge as we discussed before.…”
Section: Resultsmentioning
confidence: 53%
“…In previous work, we studied the strain effect of Sn incorporation inside Ge network involved in identical Ge and Sn layers with the present work using XRD technique. 15 The interdiffusion between Sn and Ge interfaces was demonstrated using FESEM and HRTEM. It was shown that there is a compressive strain of Ge network in its interface with Si buffer due to the mismatching between Si and Ge lattice constants and atomic radii.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been numerous reports about the dark current densities of GeSn-based PDs [31][32][33][34][35][36][37][38][39][40], very little has been done to clarify the various contributors to the dark-current-density GeSn PDs with different Sn concentrations and the effect of defect density, limiting the optimization of GeSn PDs to achieve uncooled and high-performance MIR photodetection. A few recent experimental studies have shed light on the contributing components of dark currents, such as minority carrier diffusion, Shockley-Read-Hall (SRH) generation-recombination (GR), and trap-assisted tunneling (TAT), providing evidence that the dark current of GeSn PDs is lower with lower defect densities [41][42][43]. This intended to further study the effect of defect density on the PD performance by establishing a theoretical model upon which material and device developers can form realistic expectations in developing GeSn PD architectures for various applications.…”
Section: Introductionmentioning
confidence: 99%